O preço da emoção: as transformações no custo do lazer futebolístico no Estádio Mineirão entre 1994 e 2018 - Felipe Pereira de Queiroz (2019)
Football and, more specifically, supporting in stadiums is part of the Brazilian social imaginary as a typically popular leisure. The discussions, based on the choice of Brazil as host of the 2014 World Cup, surrounding the transformations that involved this practice, were based on the various issues in the economic dimension. The increase in the price of admission, the centrality of the debate, was shown as the main reason for a perception, shared in the media, of elitisation and consequent exclusion in supporting in stages. Therefore, the present research sought to understand the economic transformations that occurred in the cost of soccer leisure in the Mineirão stadium between 1994 and 2018. For this, the behavior in the price of the tickets during the period was traced correlating with representative economic variables, inflation and percentage of the minimum wage. In addition, the occupation rate of the stadium was recorded throughout the period, in order to reflect on the observed demand. The source used to consult the information tabulated in a database was the datasheets known as Borderôs. These documents were available on the official website of the Mineirão Stadium. The methodology used to analyze the records in the database was the descriptive statistics. In addition to the analyzes of the general aggregate scenario and specific cases such as the World Cup period of 2014 and the Brazilian Championship of 1999, a set of charts for each championship were presented, namely: Brasileirão; Mineiro Championship; Brazil's Cup; Liberators; South American Cup. The data treated were able to show graphically the evolution of the prices of the tickets so that it was possible to identify patterns and infer about internal and external phenomena that influence the supporting in stages. The choice of the representative variables fulfilled the function of dimensioning the economic results for the public and academic debate. Some findings were identified as more relevant in explaining the transformations. The first one is the low correlation with observed inflation, allowing to infer that the price of the inflows is little influenced by the general behavior of market prices. However, from the point of view of the average income of the supporter, it is observed that the macroeconomic changes, such as the real increase of the minimum wage, contribute to the dimension of the opportunity cost involved in the decision to go to the stadium. It was found that with the re-inauguration of the Mineirão for the World Cup ticket prices, which previously presented a relative stability between the different moments of the competition, began to work with short-term variations. Prices have become dynamic, according to the public expectation of the game or the competition. The percentage proportion in increases in games, or competitions of greater appeal, observed from 2013, promoted an elitism and consequent exclusion in the access to certain types of emotion. On the other hand, in the aggregate scenario, with the exception of the triennium 2013-2015, this perception is relativized, insofar as prices presented an equivalence if we compare the beginning and the end of the series. The most observed average of the occupation rate did not reach 30% of the capacity of the stadium. In the years 2013, 2014 and 2018, this average is close to 50%. Therefore, the research proposed a more in-depth reflection, from an economic point of view, on the formation of ticket prices, understanding the potential of the rescue of the stadium as a space of economic diversity that retakes a greater centrality in the formation of the supporter, in order to promoting leisure options in the public environment, eliminating their economic barriers as much as possible, and offering access to certain types of excitement to more and more fans.